Instruction to take immediate action to remove stagnant water from the project to facilitate opportunities for other contractors and a healthy environment for all - Brac University (2023)
This record consists of general correspondence regarding the instruction to take immediate action to remove stagnant water from BRACU new campus project site to maintain health guidelines.